(untitled) (Research, Society and Development, 2020)
The gingival smile is characterized by the excessive exposure of teeth and gums during the contraction of muscle groups in the middle and lower thirds of the face and is present in many patients, which causes a disharmony in facial aesthetics. The objective of the article was to present a case report and demonstrate the treatment of gingival smile with the use of botulinum toxin type A, caused by muscle hypercontraction. The patient underwent clinical and photographic examinations to diagnose the muscles involved. The patient received the diluted botulinum toxin and was applied to the muscles slowly and continuously at the pre-demarcated points, with 2U on each point, 4U on each side, totaling 8U bilaterally. It is important to note that the objective was achieved with the use of botulinum toxin without the need for surgical procedures in bone tissue and gingival tissue. We concluded that botulinum toxin type A was a method used in conservative treatment and this treatment option remains considered successful and much less invasive among the possibilities presented for this type of facial aesthetic disorder found in some patients.